Macropinocytosis requires Gal-3 in a subset of patient-derived glioblastoma stem cells - Laetitia Seguin (Nature Portfolio, 2021)
Seguin et al demonstrated in glioblastoma patient-derived stem cells that a subset of glioblastoma tumours is dependent on macropinocytosis mediated survival through a Galectin-3/RAB10/beta 1 integrin axis. They used both genetic and pharmacologic inhibition of Galectin-3 in vivo and in vitro to identify underlying mechanisms and define a Galectin-3/macropinocytosis molecular signature, which could inform the development of anti-tumour therapeutic strategies.